Knowledge of Dentists about Hypomineralization Enamel Defects: A Cross-Sectional Study - Alice Pinheiro Costa; Fernanda Mafei Felix da Silva; Fernanda Gabriela de Fátima Vieira; Laura Guimarães Primo; Marcelo de Castro Costa (Association of Support to Oral Health Research (APESB), 2023)
Objective: To evaluate a group of Brazilian dentists on their knowledge of Molar Incisor Hypomineralization (MIH) and Hypomineralized Second Primary Molars (HSPM) related to clinical aspects, consequences, and diagnostic criteria. Material and Methods: In this cross-sectional, the participants were invited by e-mail and Whatsapp® to answer a questionnaire about their knowledge of hypomineralization enamel defects (MIH/HSPM) on the Google Forms® platform. The questionnaire comprised eight questions about personal data and multiple-choice questions about their knowledge concerning clinical aspects, diagnostic criteria of MIH/HSPM and differential diagnosis through clinical images. Chi-square test was applied with the significance level set at 5%. Results: Most participants (n = 492; 91.1%) reported having knowledge about MIH/HSPM. The general dentists gave more incorrect answers (n = 40; 65.6 %;) about dental tissues affected by MIH/HSPM. Overall, 83.3% of the dentists gave the correct answer to which dentitions are associated with this condition. In addition, most dentists presented knowledge about the consequences related to possible fractures (n= 487; 90.2%) and about an increased risk of caries (n= 479; 88.9%) in the affected teeth.  Regarding the differential diagnosis performed through clinical images, most participants gave incorrect answers (p≤0.001). Conclusion: The participants presented knowledge about the dentition associated with this condition and possible consequences related to the teeth affected by MIH/HSPM; however, they showed difficulties concerning clinical diagnostic criteria.